Journalistic Coverage of Blood Collection and Transfusion Services in European Countries: An Analysis of The Times of Malta and Le Monde - Bomfim de Souza, Mariluce Karla (Revista Española de Comunicación en Salud, 2025)
Objective: This article identified and characterized the news about blood and hemotherapy services, according to the components of the health services system, published in the main widely circulated newspapers in Malta and France. Methodology: The study was based on the 2022 publications of the Times of Malta and Le Monde, and the corpus of analysis consisted of 69 news items. Results: The results pointed to: the population - blood donors and the public in need of transfusions; the need for infrastructure - technologies and knowledge - to organize and operate the services. The distribution and layout of services was informative. With regard to management and regulation, there was a predominance of updates on blood donation criteria, regardless of the applicant’s sexual orientation. Safety and hemovigilance were cross-cutting aspects, in addition to rare content on financing. Conclusion: It can be concluded that the media are important for expanding knowledge, positioning and contributing to changing attitudes on various subjects, constituting a possibility for the elaboration of a corpus for the development of studies, analysis and theoretical reflection on health topics, highlighted here on the organization and operation of blood collection and transfusion services.